Strategy or Legitimacy? Analysis of the Role of Institutional Development Plans in Brazilian Universities - Maurício Andrade Lima; Fernando Antônio Ribeiro Serra; Thiago Coelho Soares; Carlos Rogerio Montenegro de Lima (BBR: Brazilian Business Review)
The aim of this study is to analyze whether Institutional Development Plans (IDP) are strategic documents or simply a response to seeking legitimacy in the face of regulatory pressures. This is a qualitative study based on information from 20 IDPs of Brazilian universities, categorized as private, public, community, or confessional. To analyze the IDPs, the content analysis methodology was used. As a result, it was found that most IDPs are much more descriptive documents, with operational goals and plans, than documents with strategic characteristics. On the other hand, in most of the documents analyzed, there was evidence of the importance and relevance of constructing an IDP as a benefit for the management and the university organization as a whole. It was concluded that IDPs tend to be documents that seek to provide universities with legitimacy in relation to the actors involved. In other words, they converge towards institutional isomorphism. Thus, they are not prepared, and used only due to institutional demands, but mainly due to legal impositions.